SISTEM TRACKING BERBASIS PID DAN MONITORING ARUS DAN TEGANGAN SOLAR PANEL SEBAGAI INTERNET OF THINGS - Syaiful Anwar; Nazori A Z (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
In this final project, a dual axis solar panel tracking system is designed to maximize the reception of sunlight andmonitoring the voltage and current of solar panels as the internet of things through an application on Android.This system consists of a 50 WP solar panel, a 12V battery, an LDR (Light Dependent Resistor) sensor, a voltagesensor, a current sensor, a servo motor, a motor driver and an Arduino Mega 2560 microcontroller. The systemworks on the principle of comparing light intensity to four LDR sensors for determine the direction of the light.Solar panels will be directed perpendicular to the direction of sunlight to maximize the energy produced by solarpanels. By using the PID method with PID parameter values, namely, Kp = 5; Ki = 1; Kd = 200. Four LDRsensors can follow any changes in the movement of the sun and position the solar panels perpendicular to thedirection of the sun. From the test results, it was found that solar panels can move following the direction ofsunlight from 51o at 10 o'clock to 142o at 15.00 on the west-east axis and there is a change in angle from 85o at10.00 to 72o at 15.00 on the north-south axis and the display Monitoring the current and voltage output values onthe internet makes it easier to find out the current and voltage output values of the solar panels.